Application of Butterfly Hug Therapy as an Effort to Manage Stress in the Communities with Risk Group in Jumerto sub-district, Patrang District, Jember: Penerapan Terapi Butterfly Hug Sebagai Upaya Manajemen Stres pada Masyarakat dengan Kelompok Risiko di Kelurahan Jumerto Kecamatan Patrang Kabupaten Jember (JURNAL UNEJ, 2024)
Based on the results of the assessment in RW 03 Jumerto Village, it showed that there were 45 people (12.1%) experiencing mental problems (ODMK) and 1 person (0.3%) experiencing mental disorders (ODGJ). One treatment to reduce anxiety is butterfly hug therapy. Butterfly hug therapy is a self-stimulation technique that helps eliminate feelings of anxiety and makes a person feel more relaxed. The aim of holding this community service activity is to provide health education accompanied by demonstrations related to butterfly hugs. It is hoped that people will know how to manage stress using self-management in the form of a butterfly hug. The number of health education participants was 20 people. The results of the health education evaluation showed that the majority of respondents stated that after doing it they felt much calmer, more enthusiastic about living their next life, and felt that someone was accompanying them when they were sad. This shows that butterfly hug health education can increase feelings of calm so that it can reduce feelings of anxiety.